Uterine arteries embolization for the treatment of leiomyomato sis: experience with 200 patients - Cantella S., Raúl (2016)
Objectives: To determine safety and efficacy of uterine artery embolization (UAE) for uterine volume reduction, leiomyoma size, symptoms relief and patient satisfaction. Design: Clinical retrospective and longitudinal study. Setting: Brazzini Interventional Radiology Institute. Participants: Two hundred patients who underwent a UAE. Interventions: Bilateral UAE with hydrogel microspheres and polyvinyl alcohol particles sized 500-900 microns were applied to 200 women. Follow-up was from three, six, twelve and up to 72 months, and included pre and post embolization uterine ultrasound, complications, and relevant epidemiological data. Results: The most common symptoms were menstrual abnormalities (42%) and anemia (17%), among others. Most common type of leiomyoma was intramural (54%). Median uterine and dominant fibroid volume reductions were 43.4% and 59%, respectively. Out of the 200 women, 113 had previous indication of hysterectomy, and 2 patients were treated surgically (1.02%). Visual analog scale assessment showed improvements of 6.7 points (0 to 10). 95% of the studied and treated population reported satisfaction with the treatment. Conclusions: UAE reduced uterine total volume and fibroids size, resulting in significant symptom relief. Treated patients reported improvements in quality of life and treatment satisfaction.